Corporate Well-Being Programme in COVID-19 Times. The Mahou San Miguel Case Study. - Núñez-Sánchez, José Manuel; Gómez Chacón, Ramón; Jambrino-Maldonado, Carmen; García Fernández, Jerónimo (MDPI, 2021)
Employees’ health is being affected not only by the possibility of contracting COVID-19, but by all the negative consequences that this pandemic has brought, such as confinement, social distancing, and self-isolation. In recent decades, more companies have opted for corporate wellbeing programmes in their workplaces, improving the health and quality of life of their employees. The effects generated by the current COVID-19 pandemic require these programmes to adapt to this new situation. The objective of this case study is to analyse the corporate well-being programme, in times of COVID-19, of Mahou San Miguel, a benchmark company in corporate well-being in Spain. A mixed method approach to data collection was used. The findings show the benefits achieved in its adaptation to this new physical-virtual environment. This paper could help other companies around the world to adapt their corporate well-being programmes to the new reality brought about by COVID-19.
Keywords: Trabajadores - Salud mental; Trabajo - Aspectos psicológicos; Gestión de personal - Aspectos psicológicos; COVID-19; Corporate well-being; Telework; Worker’s health; Physical inactivity; Corporate well-being programmes